Materials for hydrogen storage - Robina Merlino, Ariana Melisa (2015)
In the present article two systems studied theoretically in the Physics De-partment of the Universidad Nacional del Sur are presented. Both are related to the Physics of Ma-terials, more specifically to intermetallic hydrogen storage materials, and have been developed using self-consistent Density Functional Theory (DFT) calculations. DFT is a phenomenally successful approach to finding solutions to the fundamental expression that describes the quantum behaviour of atoms and molecules, the Schrödinger equation, in settings of practical value.Laves phases, under the representative forms cubic MgCu2 (C15) and hexagonal MgZn2 (C14) and MgNi2 (C36), have been extensively studied due to their promising behavior as solid state hy-drogen storage materials, ease of synthesis by the conventional cast methods, flexibility in tailoring the thermodynamic properties and good absorp-tion/desorption kinetics and cycle life. However, they cannot be used for technological applications because of its too strong hydride stability at room temperature.In this work we studied the hydrogen absorp-tion for Zr(Cr0.5Ni0.5)2, isostructural with the MgZn2 Laves phase, with the aim to find the most energetically favorable interstitial sites to locate hydrogen. Bulk modulus and volume cell changes due to the hydrogenation process were also ana-lyzed for this phase.According to literature, the most stable were the A2B2 sites, with an absorption energy average of -0.25 eV, followed by the AB3 sites. Bulk Modu-lus fluctuated in the range of 150 and165 GPa.